Aryl hydrocarbon‐estrogen alpha receptor‐dependent expression of miR‐206, miR‐27b, and miR‐133a suppress cell proliferation and migration in MCF‐7 cells. Issue 6 (19th February 2019) - Mobini, Keivan; Tamaddon, Gholamhossein; Fardid, Reza; Keshavarzi, Majid; Mohammadi‐Bardbori, Afshin
Abstract: The underlying functions of miR‐206, miR‐133a, miR‐27b, and miR‐21, and their link to the estrogen receptor alpha (ERα) and aryl hydrocarbon receptor (AhR) signaling pathways remain largely unexplored. In this study, we detect the expression of miR‐206, miR‐133a, miR‐27b, and miR‐21 in MCF‐7 through quantificational real‐time polymerase chain reaction assay along with the activation/inhibition of ERα and AhR receptors. Aside from this, cell proliferation and migration as well as AhR‐dependent CYP1A1 enzyme activity were measured. Here, we found that the forced increased expression of miR‐206, miR‐133a, and miR‐27b were closely associated with the suppression of MCF‐7 cell proliferation and migration. The anti‐proliferative‐metastatic effect of miR‐206, miR‐133a, and miR‐27b was probably mediated by targeting the ERα and AhR signaling pathways. Considered together, our study indicated that the overexpression of miR‐206, miR‐133a, and miR‐27b might be potential biomarkers for prognosis and therapeutic strategies in breast cancer.